PERMASALAHAN BAGI ANAK KAWIN CAMPUR UNTUK MEMILIH KEWARGANEGARAAN - Sry Rahayu Eka Pratiwi Neoe; Elfrida Ratnawati (LPPM Universitas Ekasakti Padang, 2023)
In this Era of Globalization, people’s lives have increased greatly, the increasing number of nations has led to a country becoming open or having international relations with other countries. Mixed marriages have traversed all corners of the country and society, information globalization, economy, transportation, cyberspace have increased mobility by migratingfrom one country to another, causing people to meet and communicate with various different ethnic groups, cultures, religions and the customs and communication habits allow Indonesian citizens (WNI) to carry out marriage with foreign citizens (WNA) so that what is called mixed marriages arises. Mixed marriages result in legal consequences, including the legal relationship between parents and children, especially the legal status of child citizenship. And the promulgation of Law No 12 Year 2006 about Republic Indonesia of Citizenship executing dual citizenship to children of mixed marriage gives impact to International Civil Law in which they have to obey the law of two different countries.